Strategi Pemasaran dalam Menarik Minat Beli Konsumen di Toko Busana Desa Air Hitam Laut - Nur Asiah; M. Arif Musthofa; Khusnul Yatimah; Daud Daud; Siti Fatimah; Haeran Haeran (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the marketing strategies implemented by fashion stores in Air Hitam Laut Village and their effectiveness in attracting consumer purchasing interest. This study used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The research subjects consisted of store owners, employees, and regular and regular customers. The results indicate that the marketing strategies implemented include: (1) Product Strategy, namely providing a variety of clothing tailored to consumer needs and current fashion trends; (2) Pricing Strategy, through competitive pricing and seasonal discounts; (3) Promotion Strategy, carried out verbally and digitally such as word of mouth, WhatsApp, and Facebook; (4) Location Strategy, with stores strategically located on main roads and near densely populated residential areas; and (5) Service Strategy, in the form of friendly and communicative service, which strengthens consumer loyalty.